Veelvormige dynamiek : Europa in het ancien régime, 1450-1800 - Frijhoff, Willem; Open Universiteit Nederland (OUNL); Wessels, Leonard H.M. (Heerlen : SUN, 2006)
Bibliotheek François Vercammen
Nederlands
Monografie